Method for preparing size-controllable cellulose nanocrystals by utilizing camellia oleifera fruit cattail
Through mechanical crushing, degreasing, bleaching and acid dissolution of the oleifera fruit, cellulose nanocrystals with controllable size were prepared, which solved the waste and pollution of the oleifera fruit, and achieved its high-value utilization and wide application.
Patent Information
- Application Number
- CN202510904021.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-01
- Publication Date
- 2025-08-22
AI Technical Summary
The prior art is difficult to effectively utilize the resources of oleifera fruit and pony, which leads to environmental pollution and waste of resources. At the same time, there is a lack of methods for preparing cellulose nanocrystals with controllable sizes, limiting its application scope.
Using oleifera fruit pills as raw material, through mechanical crushing, degreasing, removal of pectin and lignin, bleaching, chemical purification and acidolysis, acidolysis conditions such as time, temperature and acid solution concentration, cellulose nanocrystals with a length of 100-400 nm, a diameter of 10-30 nm and an aspect ratio of 5-20 were prepared.
The high-value utilization of oleifera fruits has been achieved, and cellulose nanocrystals with high specific surface area, high surface chemical activity and good biocompatibility have been prepared. They are widely used in the fields of photoelectric, biomedical and food industries to reduce environmental pollution.
Smart Images

Figure CN120518786A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomass nanomaterials, and in particular to a method for preparing size-controllable cellulose nanocrystals by utilizing camellia oleifera. Background Art
[0002] Camellia oleifera (Camellia oleifera Abel) is an evergreen tree, one of the world's four major woody oil-bearing tree species, along with oil palm, olive, and coconut. After the tea fruit matures, the shell (tea fruit) is removed, and the tea seeds are extracted and pressed to produce oil. The cake-like residue after oil extraction is called tea cake. Tea fruit and tea cake are the main by-products produced during the tea processing process, of which tea fruit accounts for 60% of the total weight of the fresh tea fruit. According to statistics, approximately 3 million tons of tea fruit are arbitrarily discarded or burned as agricultural and forestry waste each year, which not only leads to a large waste of resources, but also causes serious pollution to the environment. Therefore, how to improve the utilization rate of tea fruit is a problem that the current tea industry urgently needs to solve.
[0003] After analyzing the main chemical components of Camellia oleifera, researchers found that cellulose, hemicellulose and lignin are the most abundant, about 14-20wt%, 24-32wt% and 30-36wt% respectively, so it is an excellent source of cellulose. Cellulose nanocrystals are a naturally occurring, nanoscale cellulose-based material with a diameter usually less than 100nm and a length less than 500nm. As a highly ordered nanocrystalline material, cellulose nanocrystals not only retain the excellent properties of cellulose renewability and degradability, but also have excellent mechanical properties, optical properties and high specific surface area, showing a wide range of application potential. Using Camellia oleifera as raw material to prepare cellulose nanocrystals with high added value is an effective means of high-value utilization of Camellia oleifera, and has important practical significance for its sustainable green development.
[0004] Size control is a key issue in the preparation of cellulose nanocrystals. Because different applications require different sizes for cellulose nanocrystals, developing a method for preparing size-controlled cellulose nanocrystals from cattail oil palm is crucial. This will not only help improve the product's performance and quality, but also broaden its application areas. Summary of the Invention
[0005] In view of this, the present invention addresses the deficiencies in the prior art, and its main purpose is to provide a method for preparing size-controllable cellulose nanocrystals using camellia oleifera. By adopting the method provided by the present application, the size morphology of cellulose nanocrystals can be flexibly controlled, effectively solving the problems of environmental pollution and resource waste generated during the processing of camellia oleifera. The production process of this method is simple, the reaction is efficient, and it is easy to implement. The prepared camellia oleifera cellulose nanocrystals have a high specific surface area, high surface chemical activity, good biocompatibility and degradability, and can be widely used in optoelectronics, biomedicine and food industries.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing size-controlled cellulose nanocrystals using camellia oleifera, comprising the following steps:
[0008] S1, using cattail oil-leaf twigs as raw materials and mechanically crushing them to obtain cattail oil-leaf twig powder;
[0009] S2, defatting the oil-tea camellia cattail powder to obtain defatted oil-tea camellia cattail powder;
[0010] S3, removing pectin from the defatted camellia oleifera fruit powder to obtain a crude product;
[0011] S4, removing lignin and pigment from the crude product to obtain bleached camellia oleifera cellulose;
[0012] S5, removing hemicellulose from the bleached camellia cellulose to obtain chemically purified camellia cellulose;
[0013] S6. Acid hydrolysis of chemically purified camellia oleifera cellulose to prepare cellulose nanocrystals;
[0014] S7, purification of cellulose nanocrystals;
[0015] The acid hydrolysis conditions in step S6 are as follows: the acid hydrolysis time is 30-75 minutes, the acid hydrolysis temperature is 40-55°C, and the concentration of the acid solution used in the acid hydrolysis is 58-67%; the length of the obtained cellulose nanocrystals is 100-400 nm, the diameter is 10-30 nm, and the aspect ratio is 5-20; and the size-controllable cellulose nanocrystals are obtained by adjusting the acid hydrolysis conditions.
[0016] As a preferred solution: the step S1 specifically comprises: mechanically crushing and sieving the dried cattail oil tree fruit to obtain cattail oil tree fruit powder, wherein the sieving is through a 60-150 mesh sieve.
[0017] As a preferred solution: Step S2 specifically comprises: adding cattail oil-tea cattail powder to a non-polar solvent, stirring at room temperature for 1-8 hours, and then performing solid-liquid separation using a vacuum filter, collecting the filter residue, and heating it in a vacuum oven at 30-80° C. for 1-8 hours to obtain dry defatted cattail oil-tea cattail powder; the solid-liquid ratio of the cattail oil-tea cattail powder to the polar solvent is 1 g:10 mL-1 g:50 mL; and the non-polar solvent used is ethanol, isopropanol, or petroleum ether, which is a non-polar solvent that can dissolve oils and fats.
[0018] As a preferred solution: Step S3 is specifically as follows: adding the defatted Camellia oleifera powder to distilled water, adding an acidic reagent dropwise thereto, adjusting the pH to an appropriate range, and then stirring in a 70-90°C water bath for 2-4 hours, collecting the solid after centrifugation and washing, and drying it to obtain a crude product.
[0019] As a preferred embodiment: Step S4 specifically comprises: adding the crude product to a sodium chlorite solution, adjusting the pH of the solution to 2-5, stirring in a water bath at 50-90° C. for 1-5 hours, filtering and washing the precipitate with water until neutral, repeating the bleaching process 3-9 times until a white product is obtained; heating the white product in an oven at 40-60° C. for 4-8 hours to dry it to obtain bleached camellia cellulose; the concentration of the sodium chlorite solution is 1-5% (w / v); and the material-liquid ratio of the crude product to the sodium chlorite solution is 1 g:10 mL to 1 g:30 mL.
[0020] As a preferred embodiment: Step S5 specifically comprises: adding the bleached camellia cellulose to a sodium hydroxide solution and performing a water bath heating reaction, then washing the precipitate to neutrality, collecting the solid to obtain chemically purified camellia cellulose; the concentration of the sodium hydroxide solution is 4-10% (w / v); the material-liquid ratio of the bleached camellia cellulose to the sodium hydroxide solution is 1 g:15 mL-1 g:45 mL, and the water bath heating reaction is performed at 50-85° C. for 2-6 hours.
[0021] As a preferred solution: Step S6 is specifically as follows: dispersing the chemically purified camellia oleifera cellulose in an acidic solution, stirring the reaction in a water bath at 30-90°C for 20-100 minutes, then adding 10-15 times the volume of 4°C pre-cooled deionized water to terminate the reaction, and centrifuging and washing several times to obtain a camellia oleifera cellulose nanocrystal suspension.
[0022] As a preferred embodiment: Step S7 specifically comprises: purifying the prepared cellulose nanocrystals by dialysis, placing the oil-tea camellia cellulose nanocrystal suspension into a dialysis bag, dialyzing with deionized water until the pH of the suspension is neutral, and then performing ultrasonic dispersion treatment to obtain a purified oil-tea camellia cellulose nanocrystal aqueous solution; the molecular weight cut-off of the dialysis bag is 8000-14000Da; the ultrasonic treatment is carried out in an ice bath, the ultrasonic power is 200-600w, and the ultrasonic time is 2-10min.
[0023] As a preferred solution: in step S3, the material-liquid ratio of cattail oil palm powder to distilled water is 1g:5mL-1g:50mL; the acidic reagent added dropwise is hydrochloric acid, sulfuric acid or nitric acid, with a concentration of 0.1-1mol / L; the suitable pH range after adjustment is 1-3; the centrifugation conditions are: speed 2000-5000rpm, centrifugation time 2-8min; and the drying conditions are: drying at 40-90°C for 3-12h.
[0024] As a preferred embodiment: the acidic solution selected in step S6 includes an inorganic acid and an organic acid, the inorganic acid includes sulfuric acid, hydrochloric acid or phosphoric acid, and the organic acid includes formic acid or oxalic acid; the material-liquid ratio of chemically purified camellia cellulose to the acidic solution is 1g:10mL-1g:50mL; the centrifugation conditions are centrifugation at a speed of 8000-12000rpm for 8-30min.
[0025] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:
[0026] First, a method for preparing size-controllable cellulose nanocrystals using camellia oleifera is provided. Cellulose nanocrystals of different sizes are prepared from camellia oleifera. This method provides a new technical approach for the high-value utilization of camellia oleifera resources and realizes the size control of cellulose nanocrystals.
[0027] Second, the present invention's production process for the production of oil-tea camellia cellulose nanocrystals is simple, highly efficient, and easy to implement. By varying the sulfuric acid hydrolysis conditions, the size and morphology of the cellulose nanocrystals can be flexibly controlled. The resulting oil-tea camellia cellulose nanocrystals possess high specific surface area, high surface chemical activity, excellent biocompatibility, and biodegradability, making them suitable for a wide range of applications in the optoelectronics, biomedical, and food industries.
[0028] Third, the present invention uses Camellia oleifera as raw material to prepare cellulose nanocrystals, which effectively utilizes waste resources and reduces environmental pollution while achieving high-value utilization of Camellia oleifera.
[0029] To more clearly illustrate the structural features and effects of the present invention, it is described in detail below with reference to the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic diagram comparing the scanning electron microscopy results of the raw material Camellia oleifera and the extracted Camellia oleifera cellulose in Example 1 of the present invention;
[0031] Figure 2 This is a scanning electron microscope image of the Camellia oleifera cellulose nanocrystals obtained in Example 1 of the present invention;
[0032] Figure 3 This is a scanning electron microscope image of the Camellia oleifera cellulose nanocrystals obtained in Example 2 of the present invention;
[0033] Figure 4 This is a transmission electron micrograph of the Camellia oleifera cellulose nanocrystals obtained in Example 2 of the present invention;
[0034] Figure 5 This is an optical image of the Camellia oleifera cellulose nanocrystals obtained in Example 3 of the present invention;
[0035] Figure 6 This is a scanning electron microscope image of the Camellia oleifera cellulose nanocrystals obtained in Example 3 of the present invention;
[0036] Figure 7 This is a scanning electron microscope image of the camellia oleifera cellulose nanocrystals obtained in Example 4 of the present invention.
[0037] Description of the accompanying drawings:
[0038] In the picture: Figure 1 A in the middle is the raw material Camellia oleifera, Figure 1 B in the middle is the cellulose extracted from camellia oleifera fruit. DETAILED DESCRIPTION
[0039] The present invention Figures 1 to 7 As shown, a method for preparing size-controlled cellulose nanocrystals using camellia oleifera fruit comprises the following steps:
[0040] S1, using cattail oil-leaf twigs as raw materials and mechanically crushing them to obtain cattail oil-leaf twig powder;
[0041] S2, defatting the oil-tea camellia cattail powder to obtain defatted oil-tea camellia cattail powder;
[0042] S3, removing pectin from the defatted camellia oleifera fruit powder to obtain a crude product;
[0043] S4, removing lignin and pigment from the crude product to obtain bleached camellia oleifera cellulose;
[0044] S5, removing hemicellulose from the bleached camellia cellulose to obtain chemically purified camellia cellulose;
[0045] S6. Acid hydrolysis of chemically purified camellia oleifera cellulose to prepare cellulose nanocrystals;
[0046] S7, purification of cellulose nanocrystals;
[0047] The acid hydrolysis conditions in step S6 are as follows: the acid hydrolysis time is 30-75 minutes, the acid hydrolysis temperature is 40-55°C, and the concentration of the acid solution used in the acid hydrolysis is 58-67%; the length of the obtained cellulose nanocrystals is 100-400 nm, the diameter is 10-30 nm, and the aspect ratio is 5-20; and the size-controllable cellulose nanocrystals are obtained by adjusting the acid hydrolysis conditions.
[0048] The step S1 specifically comprises: mechanically crushing and sieving the dried cattail oil leaves in sequence to obtain cattail oil leaves powder, wherein the sieving is performed through a 60-150 mesh sieve.
[0049] The step S2 specifically comprises: adding cattail oil-tea cattail powder to a non-polar solvent, stirring at room temperature for 1-8 hours, and then performing solid-liquid separation by a vacuum filter, collecting the filter residue, and heating it in a vacuum oven at 30-80° C. for 1-8 hours to obtain dry defatted cattail oil-tea cattail powder; the solid-liquid ratio of the cattail oil-tea cattail powder to the polar solvent is 1 g:10 mL-1 g:50 mL; and the non-polar solvent used is ethanol, isopropanol, or petroleum ether, which are non-polar solvents that can dissolve oils and fats.
[0050] The specific steps of step S3 are as follows: adding the defatted camellia oleifera powder to distilled water, adding an acidic reagent dropwise thereto, adjusting the pH to a suitable range, and then stirring in a 70-90° C. water bath for 2-4 hours, collecting the solid after centrifugation and washing, and drying it to obtain a crude product.
[0051] Step S4 specifically comprises: adding the crude product to a sodium chlorite solution, adjusting the pH of the solution to 2-5, stirring in a water bath at 50-90° C. for 1-5 hours, filtering and washing the precipitate with water until neutral, and repeating the bleaching process 3-9 times until a white product is obtained; heating the white product in an oven at 40-60° C. for 4-8 hours to dry it to obtain bleached camellia cellulose; the concentration of the sodium chlorite solution is 1-5% (w / v); and the material-liquid ratio of the crude product to the sodium chlorite solution is 1 g:10 mL to 1 g:30 mL.
[0052] The specific steps of step S5 are as follows: adding the bleached camellia cellulose to a sodium hydroxide solution and performing a water bath heating reaction; then washing the precipitate to neutrality, collecting the solid to obtain chemically purified camellia cellulose; the concentration of the sodium hydroxide solution is 4-10% (w / v); the material-liquid ratio of the bleached camellia cellulose to the sodium hydroxide solution is 1 g:15 mL-1 g:45 mL, and the water bath heating reaction is performed at 50-85° C. for 2-6 hours.
[0053] The specific steps of step S6 are as follows: dispersing the chemically purified camellia oleifera cellulose in an acidic solution, stirring the solution in a water bath at 30-90° C. for 20-100 minutes, adding 10-15 times the volume of 4° C. pre-cooled deionized water to terminate the reaction, and centrifuging and washing the solution several times to obtain a camellia oleifera cellulose nanocrystal suspension.
[0054] The specific steps of step S7 are as follows: purifying the prepared cellulose nanocrystals by dialysis, placing the oil-tea camellia cellulose nanocrystal suspension into a dialysis bag, dialyzing with deionized water until the pH of the suspension is neutral, and then performing ultrasonic dispersion treatment to obtain a purified oil-tea camellia cellulose nanocrystal aqueous solution; the molecular weight cutoff of the dialysis bag is 8000-14000Da; and the ultrasonic treatment is performed in an ice bath, the ultrasonic power is 200-600w, and the ultrasonic time is 2-10min.
[0055] In step S3, the material-liquid ratio of cattail oil palm powder to distilled water is 1g:5mL-1g:50mL; the acidic reagent added dropwise is hydrochloric acid, sulfuric acid or nitric acid, with a concentration of 0.1-1mol / L; the appropriate pH range after adjustment is 1-3; the centrifugation conditions are: speed 2000-5000rpm, centrifugation time 2-8min; and the drying conditions are: drying at 40-90°C for 3-12h.
[0056] The acidic solution selected in step S6 includes an inorganic acid and an organic acid, the inorganic acid includes sulfuric acid, hydrochloric acid or phosphoric acid, and the organic acid includes formic acid or oxalic acid; the material-liquid ratio of chemically purified camellia oleifera cellulose to the acidic solution is 1g:10mL-1g:50mL; the centrifugation condition is centrifugation at a speed of 8000-12000rpm for 8-30min.
[0057] Prior art related to the present invention
[0058] Through aerobic composting technology, oil-tea camellia waste can be fermented and transformed into high-efficiency organic fertilizer for agricultural production. However, compared with organic fertilizers such as livestock manure or soybean cake, the content of major nutrients such as nitrogen, phosphorus, and potassium in oil-tea camellia is relatively low, making it difficult to use as a single fertilizer source to meet the needs of high-yield crops. In addition, oil-tea camellia contains a lot of lignin, hemicellulose, and cellulose. These components have stable structures and decompose slowly. Direct application may lead to insufficient nutrient release in the short term and cannot meet the nutritional needs of crops during the rapid growth period.
[0059] Prior art 2 related to the present invention
[0060] Cellulose nanocrystals are prepared by using 2,2,6,6-tetramethylpiperidinyl oxide (TEMPO) as an oxidation catalyst to selectively oxidize the hydroxyl group at the C6 position of cellulose into a carboxyl group. Two TEMPO oxidation systems are generally used, depending on the pH of the reaction system: a TEMPO / NaBr / NaClO system is used under alkaline conditions (pH 10-11); and a TEMPO / NaClO / NaClO2 system is generally used under acidic conditions (pH 4.8-6.8). The TEMPO oxidation method has the advantages of mild reaction conditions, strong operability, and high yield. However, the TEMPO reagent is expensive, costly, and toxic, which limits its application.
[0061] Example 1
[0062] S1. Mechanical grinding: grinding the dried cattail oil tree fruit and passing it through an 80-mesh sieve to obtain cattail oil tree fruit powder;
[0063] S2, defatting: take an appropriate amount of the cattail oil palm powder obtained in step S1 and add it to petroleum ether at a material-liquid ratio of 1:10 (m / v), stir at room temperature for 3 h, filter and obtain a residue, and dry it at 60°C for 3 h;
[0064] S3, pectin removal: the filter residue obtained in step S2 was added to distilled water at a solid-liquid ratio of 1:20 (m / v), 1 mol / L hydrochloric acid was added dropwise to adjust the pH to 2, and the mixture was stirred in an 85°C water bath for 2.5 h. The insoluble solid was washed and centrifuged, and then dried at 70°C for 5 h.
[0065] S4, removal of lignin and pigments: the crude product obtained in step S3 was added to a 5% (w / v) sodium chlorite solution at a material-liquid ratio of 1:10 (m / v), the pH of the solution was adjusted to 4, and the mixture was stirred in a 75°C water bath for 2 hours. The precipitate was filtered and washed with water until neutral, and the bleaching process was repeated 4 times until a white product was obtained, which was then dried at 60°C for 6 hours to obtain bleached camellia cellulose;
[0066] S5. Removal of hemicellulose: adding the bleached camellia cellulose obtained in step S4 to a 10% (w / v) sodium hydroxide solution at a material-liquid ratio of 1:30 (m / v), stirring in an 80°C water bath for 3 hours, washing the precipitate until neutral, then filtering it with suction and drying it at 60°C for 6 hours to obtain chemically purified camellia cellulose;
[0067] S6. Preparation of cellulose nanocrystals: The chemically purified camellia oleifera cellulose obtained in step S5 was dispersed in a 61% (w / v) sulfuric acid solution at a solid-liquid ratio of 1:20 (m / v), stirred in a water bath at 45° C. for 30 min, and then 10 times the volume of 4° C. pre-cooled deionized water was added to terminate the reaction. The mixture was centrifuged at 10,000 rpm / min for 15 min and washed twice by centrifugation to obtain a camellia oleifera cellulose nanocrystal suspension;
[0068] S7. Purification of cellulose nanocrystals: The oil-tea camellia cellulose nanocrystal suspension obtained in step S6 was placed in a dialysis bag with a molecular weight cutoff of 8000-14000Da, and dialyzed with deionized water until the pH of the suspension was neutral. The suspension was then subjected to ultrasonic dispersion treatment in an ice bath with an ultrasonic power of 325W, an ultrasonic time of 5min, a working time of 8s, and an interval time of 2s to obtain an aqueous solution of oil-tea camellia cellulose nanocrystals.
[0069] The cellulose extracted from the oil-tea camellia fruit obtained in Example 1 was compared with the raw material oil-tea camellia fruit by scanning electron microscopy. Figure 1 :Depend on Figure 1 In A, it can be found that the surface structure of the original Camellia oleifera is dense and smooth, with irregular impurities attached; Figure 1 In B, the oil-tea camellia cellulose obtained after being treated by the method of the present invention is shown, which exhibits obvious exposed fiber filaments and an interwoven structural feature.
[0070] The scanning electron microscope image of the oil-tea camellia fruit cellulose nanocrystals obtained in Example 1 is attached. Figure 2 ,Depend on Figure 2 It can be seen that the prepared cellulose nanocrystals have a rod-like structure and are relatively long overall.
[0071] Example 2
[0072] S1. Mechanical grinding: grinding the dried cattail oil tree fruit and passing it through an 80-mesh sieve to obtain cattail oil tree fruit powder;
[0073] S2, defatting: take an appropriate amount of cattail oil palm powder obtained in step S1 and add it to petroleum ether at a material-liquid ratio of 1:10 (m / v), stir at room temperature for 3 hours, filter and obtain a residue, and dry it in a 60°C oven for 3 hours;
[0074] S3, removal of pectin: the filter residue obtained in step S2 was added to distilled water at a material-liquid ratio of 1:20 (m / v), 1 mol / L hydrochloric acid was added dropwise to adjust the pH to 2, and the mixture was stirred in an 85°C water bath for 2.5 h. The insoluble solid was washed and centrifuged, and then dried in a 70°C oven for 5 h;
[0075] S4, removal of lignin and pigments: the crude product obtained in step S3 was added to a 5% (w / v) sodium chlorite solution at a material-liquid ratio of 1:10 (m / v), the pH of the solution was adjusted to 4, and the mixture was stirred in a 75°C water bath for 2 hours. The precipitate was filtered and washed with water until neutral. The bleaching process was repeated 4 times until a white product was obtained, which was then dried in an oven at 60°C for 6 hours to obtain bleached camellia cellulose.
[0076] S5. Removal of hemicellulose: adding the bleached camellia cellulose obtained in step S4 to a 10% (w / v) sodium hydroxide solution at a solid-liquid ratio of 1:30 (m / v), stirring in an 80°C water bath for 3 hours, washing the precipitate to neutrality, then filtering it with suction and drying it in an oven at 60°C for 6 hours to obtain chemically purified camellia cellulose;
[0077] S6. Preparation of cellulose nanocrystals: The chemically purified camellia oleifera cellulose obtained in step S5 was dispersed in a 61% (w / v) sulfuric acid solution at a solid-liquid ratio of 1:20 (m / v), stirred in a water bath at 45°C for 60 min, and then 10 times the volume of 4°C pre-cooled deionized water was added to terminate the reaction. The mixture was centrifuged at 10,000 rpm / min for 15 min and washed twice by centrifugation to obtain a camellia oleifera cellulose nanocrystal suspension;
[0078] S7. Purification of cellulose nanocrystals: The oil-tea camellia cellulose nanocrystal suspension obtained in step S6 was placed in a dialysis bag with a molecular weight cutoff of 8000-14000Da, and dialyzed with deionized water until the pH of the suspension was neutral. The suspension was then subjected to ultrasonic dispersion treatment in an ice bath with an ultrasonic power of 325W, an ultrasonic time of 5min, a working time of 8s, and an interval time of 2s to obtain an aqueous solution of oil-tea camellia cellulose nanocrystals.
[0079] The scanning electron microscope image of the oil-tea camellia fruit cellulose nanocrystals obtained in Example 2 is attached. Figure 3 ,Depend on Figure 3 It can be seen that the prepared cellulose nanocrystals are still rod-shaped, but a small amount of needle-like structures appear. As the acid hydrolysis time increases, the size of the cellulose nanocrystals decreases.
[0080] The results of the transmission electron microscope analysis of the oil-tea camellia fruit cellulose nanocrystals prepared in Example 2 can be confirmed (see the attached Figure 4 ), the prepared cellulose nanocrystals still exhibited a typical rod-like structure. Their size and morphology parameters were consistent with the scanning electron microscopy results, further verifying the reliability of the preparation process.
[0081] Example 3
[0082] S1. Mechanical grinding: grinding the dried cattail oil tree fruit and passing it through an 80-mesh sieve to obtain cattail oil tree fruit powder;
[0083] S2, defatting: take an appropriate amount of cattail oil palm powder obtained in step S1, add it to petroleum ether at a ratio of 1:10 (m / v), stir it at room temperature for 3 hours, filter it to obtain a residue, and dry it at 60°C for 3 hours;
[0084] S3, pectin removal: the filter residue obtained in step S2 was added to distilled water at a ratio of 1:20 (m / v), 1 mol / L hydrochloric acid was added dropwise to adjust the pH to 2, and the mixture was stirred continuously in an 85°C water bath for 2.5 h. The insoluble solid was washed and centrifuged, and then dried at 70°C for 5 h.
[0085] S4, removal of lignin and pigments: the crude product obtained in step S3 was added to a 5% (w / v) sodium chlorite solution at a ratio of 1:10 (m / v), the pH of the solution was adjusted to 4, and the mixture was stirred in a 75°C water bath for 2 hours. The precipitate was filtered and washed with water until neutral, and the bleaching process was repeated 4 times until a white product was obtained, which was then dried at 60°C for 6 hours to obtain bleached camellia cellulose.
[0086] S5. Removal of hemicellulose: adding the bleached camellia cellulose obtained in step S4 to a 10% (w / v) sodium hydroxide solution at a ratio of 1:30 (m / v), stirring continuously in an 80°C water bath for 3 hours, washing the precipitate until neutral, then filtering it with suction and drying it at 60°C for 6 hours to obtain chemically purified camellia cellulose;
[0087] S6. Preparation of cellulose nanocrystals: The chemically purified camellia oleifera cellulose obtained in step S5 was dispersed in a 61% (w / v) sulfuric acid solution at a ratio of 1:20 (m / v), and the mixture was stirred in a water bath at 50° C. for 60 min. 10 times the volume of 4° C. pre-cooled deionized water was added to terminate the reaction, and the mixture was centrifuged at 10,000 rpm / min for 15 min. The mixture was washed twice by centrifugation to obtain a camellia oleifera cellulose nanocrystal suspension.
[0088] S7. Purification of cellulose nanocrystals: The oil-tea camellia cellulose nanocrystal suspension obtained in step S6 was placed in a dialysis bag with a molecular weight cutoff of 8000-14000Da, and dialyzed with deionized water until the pH of the suspension reached neutral. The suspension was then subjected to ultrasonic dispersion treatment in an ice bath with an ultrasonic power of 325W, an ultrasonic time of 5min, a working time of 8s, and an interval time of 2s to obtain an aqueous solution of oil-tea camellia cellulose nanocrystals.
[0089] The optical image of the Camellia oleifera cellulose nanocrystals obtained in Example 3 is attached. Figure 5 ,Depend on Figure 5The resulting aqueous solution of cellulose nanocrystals exhibits a stable, pale blue colloidal state. Infrared irradiation reveals a distinct "Tyndall pathway," indicating that the cellulose nanocrystal particles in the aqueous solution have reached nanoscale dimensions. The zeta potential of the aqueous solution was measured to be -33.1 mV (pH = 6.2), and no flocculation was observed after 60 days at room temperature, demonstrating its excellent stability. In summary, the prepared aqueous solution of cellulose nanocrystals exhibits nanoscale dispersion and a stable colloidal system.
[0090] The scanning electron microscope image of the oil-tea camellia fruit cellulose nanocrystals obtained in Example 3 is attached. Figure 6 ,Depend on Figure 6 It can be seen that the prepared cellulose nanocrystals are mainly rod-like structures, and also include some needle-like structures, with good size uniformity. As the reaction temperature increases, the size of the cellulose nanocrystals decreases.
[0091] Example 4
[0092] S1. Mechanical crushing: crush the dried cattail oil tree fruit and pass it through an 80-mesh sieve to obtain cattail oil tree fruit powder;
[0093] S2, defatting: take an appropriate amount of the cattail oil-tea tree powder obtained in step S1 and add it to petroleum ether at a material-liquid ratio of 1:10 (m / v), stir at room temperature for 3 hours, then filter to obtain a residue, and dry it at 60°C for 3 hours;
[0094] S3, pectin removal: the filter residue obtained in step S2 was added to distilled water at a solid-liquid ratio of 1:20 (m / v), the pH was adjusted to 2 with 1 mol / L hydrochloric acid, and the mixture was stirred in an 85°C water bath for 2.5 h. The insoluble solid was washed by centrifugation and dried at 70°C for 5 h.
[0095] S4, removal of lignin and pigments: the crude product obtained in step S3 was mixed with 5% (w / v) sodium chlorite solution at a ratio of 1:10 (m / v), the pH of the solution was adjusted to 4, and the mixture was stirred in a 75°C water bath for 2 hours. The mixture was filtered and washed with water until the precipitate was neutral. The bleaching process was repeated 4 times until a white product was obtained, which was then dried at 60°C for 6 hours to obtain bleached camellia cellulose.
[0096] S5. Removal of hemicellulose: The bleached camellia cellulose obtained in step S4 was mixed with 10% (w / v) sodium hydroxide solution at a ratio of 1:30 (m / v), stirred in an 80°C water bath for 3 hours, and the precipitate was washed with water until neutral, then filtered and dried at 60°C for 6 hours to obtain chemically purified camellia cellulose;
[0097] S6. Preparation of cellulose nanocrystals: The chemically purified camellia oleifera cellulose obtained in step S5 was dispersed in a 64% (w / v) sulfuric acid solution at a material-liquid ratio of 1:20 (m / v), and the mixture was stirred in a water bath at 45° C. for 60 min. Ten volumes of 4° C. pre-cooled deionized water were added to terminate the reaction, and the mixture was centrifuged at 10,000 rpm / min for 15 min. The mixture was washed twice by centrifugation to obtain a camellia oleifera cellulose nanocrystal suspension.
[0098] S7. Purification of cellulose nanocrystals: The oil-tea camellia cellulose nanocrystal suspension obtained in step S6 was placed in a dialysis bag with a molecular weight cutoff of 8000-14000Da, and dialyzed with deionized water until the pH of the suspension was neutral. The suspension was then ultrasonically treated in an ice bath to uniformly disperse the suspension. The ultrasonic power was 325W, the ultrasonic time was 5min, the working time and the interval time were 8s and 2s respectively, to obtain an oil-tea camellia cellulose nanocrystal aqueous solution.
[0099] The scanning electron microscope image of the oil-tea camellia fruit cellulose nanocrystals obtained in Example 4 is attached. Figure 5 ,Depend on Figure 5 It can be seen that the prepared cellulose nanocrystals have a rod-like or needle-like structure, and the size of the cellulose nanocrystals decreases with the increase of sulfuric acid concentration.
[0100] Analysis of Examples 1 to 4:
[0101] In Examples 1 to 4 of the present invention, camellia oleifera cellulose was obtained from camellia oleifera cellulose by petroleum ether degreasing, acid pectin removal, sodium chlorite bleaching, and alkali purification. The cellulose nanocrystals were then hydrolyzed with sulfuric acid and then centrifuged and ultrasonically dispersed. The yield, length, and diameter of the cellulose nanocrystals finally prepared were measured. The specific measurement results are shown in Table 1.
[0102] Table 1: Yield, average length and diameter of cellulose nanocrystals prepared in Examples 1 to 4
[0103] sample Yield (%) Average length (nm) Average diameter (nm) Aspect ratio Example 1 69.4 260.6±3.7 21.5±0.4 12.1 Example 2 67.4 220.1±3.2 20.1±0.3 11.0 Example 3 63.7 191.4±2.8 19.1±0.2 10.1 Example 4 29.4 151.5±2.6 17.6±0.2 8.6
[0104] As can be seen from Table 1, the yield of cellulose nanocrystals from oil-tea camellia calyx obtained by the preparation method of the present invention is between 29.4% and 69.4%. By adjusting the acid hydrolysis time (30-60min) and the acid hydrolysis temperature (40-45°C), the yield of cellulose nanocrystals is maintained within a fluctuation range of approximately 65%. However, when the sulfuric acid concentration is increased from 61% to 64%, the yield drops significantly to 29.4%. This result shows that the change in sulfuric acid concentration has the most significant effect on the yield of cellulose nanocrystals. The average length of the prepared oil-tea camellia calyx cellulose nanocrystals is 151.5-260.6nm, the average diameter is 17.6-21.5nm, and the aspect ratio is 8.6-12.1, all of which are in the nanometer size range, which is consistent with the size characteristics of cellulose nanocrystals. Combined with transmission electron microscopy images, the oil-tea camellia calyx cellulose nanocrystals present rod-shaped or needle-shaped morphology. With increasing acid hydrolysis time (30-75 minutes), acid hydrolysis temperature (40-55°C), or sulfuric acid concentration (58-67%), the length (120-320 nm) and diameter (14-24 nm) of the cellulose nanocrystals decreased continuously, and their size distribution became more uniform, with the aspect ratio (6-18) gradually decreasing. By regulating the acid hydrolysis conditions, the size of the cellulose nanocrystals was successfully controlled.
[0105] The present invention has a simple production process and efficient reaction. By varying the acid hydrolysis conditions (acid hydrolysis time, acid hydrolysis temperature, and sulfuric acid concentration), the size and morphology of the cellulose nanocrystals can be flexibly controlled to meet the needs of different application areas. Furthermore, the invention realizes the high-value utilization of oil-tea camellia cattails as an agricultural and forestry waste, which has important economic and environmental significance. The obtained oil-tea camellia cattail cellulose nanocrystals, due to their excellent physical and chemical properties, can be widely used in the optoelectronics, biomedical, and food industries.
[0106] The design emphasis of the present invention is:
[0107] First, a method for preparing size-controllable cellulose nanocrystals using camellia oleifera is provided. Cellulose nanocrystals of different sizes are prepared from camellia oleifera. This method provides a new technical approach for the high-value utilization of camellia oleifera resources and realizes the size control of cellulose nanocrystals.
[0108] Second, the present invention's production process for the production of oil-tea camellia cellulose nanocrystals is simple, highly efficient, and easy to implement. By varying the sulfuric acid hydrolysis conditions, the size and morphology of the cellulose nanocrystals can be flexibly controlled. The resulting oil-tea camellia cellulose nanocrystals possess high specific surface area, high surface chemical activity, excellent biocompatibility, and biodegradability, making them suitable for a wide range of applications in the optoelectronics, biomedical, and food industries.
[0109] Third, the present invention uses Camellia oleifera as raw material to prepare cellulose nanocrystals, which effectively utilizes waste resources and reduces environmental pollution while achieving high-value utilization of Camellia oleifera.
[0110] The above description is merely a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any minor modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing size-controlled cellulose nanocrystals using Camellia oleifera, characterized by: The steps include: S1, using cattail oil-leaf twigs as raw materials and mechanically crushing them to obtain cattail oil-leaf twig powder; S2, defatting the oil-tea camellia cattail powder to obtain defatted oil-tea camellia cattail powder; S3, removing pectin from the defatted camellia oleifera fruit powder to obtain a crude product; S4, removing lignin and pigment from the crude product to obtain bleached camellia oleifera cellulose; S5, removing hemicellulose from the bleached camellia cellulose to obtain chemically purified camellia cellulose; S6. Acid hydrolysis of chemically purified camellia oleifera cellulose to prepare cellulose nanocrystals; S7, purification of cellulose nanocrystals; The acid hydrolysis conditions in step S6 are as follows: the acid hydrolysis time is 30-75 minutes, the acid hydrolysis temperature is 40-55°C, and the concentration of the acid solution used in the acid hydrolysis is 58-67%; the length of the obtained cellulose nanocrystals is 100-400 nm, the diameter is 10-30 nm, and the aspect ratio is 5-20; and the size-controllable cellulose nanocrystals are obtained by adjusting the acid hydrolysis conditions.
2. The method for preparing size-controlled cellulose nanocrystals using Camellia oleifera according to claim 1, characterized in that: The step S1 specifically comprises: mechanically crushing and sieving the dried cattail oil leaves in sequence to obtain cattail oil leaves powder, wherein the sieving is to pass through a 60-150 mesh sieve.
3. The method for preparing size-controlled cellulose nanocrystals using Camellia oleifera according to claim 1, characterized in that: The step S2 specifically comprises: adding cattail oil-tea cattail powder to a non-polar solvent, stirring at room temperature for 1-8 hours, and then performing solid-liquid separation using a vacuum filter, collecting the filter residue, and heating it in a vacuum oven at 30-80° C. for 1-8 hours to obtain dry defatted cattail oil-tea cattail powder; the solid-liquid ratio of the cattail oil-tea cattail powder to the polar solvent is 1 g:10 mL-1 g:50 mL; and the non-polar solvent used is ethanol, isopropanol, or petroleum ether, which is a non-polar solvent capable of dissolving oil and fat.
4. The method for preparing size-controlled cellulose nanocrystals using Camellia oleifera according to claim 1, wherein: The step S3 specifically comprises: adding the defatted camellia oleifera powder into distilled water, adding an acidic reagent dropwise thereto, adjusting the pH to a suitable range, and then stirring in a 70-90° C. water bath for 2-4 hours, collecting the solid after centrifugation and washing, and drying it to obtain a crude product.
5. The method for preparing size-controlled cellulose nanocrystals using Camellia oleifera according to claim 1, characterized in that: The step S4 specifically comprises: adding the crude product to a sodium chlorite solution, adjusting the pH of the solution to 2-5, stirring in a water bath at 50-90° C. for 1-5 hours, filtering and washing the precipitate with water until it is neutral, and repeating the bleaching process 3-9 times until a white product is obtained; The white product is placed in an oven and heated at 40-60° C. for 4-8 hours to obtain bleached camellia cellulose. The concentration of the sodium chlorite solution is 1-5% (w / v); the material-liquid ratio of the crude product to the sodium chlorite solution is 1 g:10 mL-1 g:30 mL.
6. The method for preparing size-controlled cellulose nanocrystals using Camellia oleifera according to claim 1, characterized in that: The step S5 specifically comprises: adding the bleached camellia cellulose to a sodium hydroxide solution, heating the solution in a water bath for reaction, washing the precipitate to neutrality, and collecting the solid to obtain chemically purified camellia cellulose; The concentration of the sodium hydroxide solution is 4-10% (w / v); the material-liquid ratio of the bleached camellia cellulose and the sodium hydroxide solution is 1g:15mL-1g:45mL, and the water bath heating reaction condition is 50-85°C for 2-6h.
7. The method for preparing size-controlled cellulose nanocrystals using Camellia oleifera according to claim 1, characterized in that: The step S6 specifically comprises: dispersing the chemically purified camellia oleifera cellulose in an acidic solution, stirring the solution in a water bath at 30-90° C. for 20-100 minutes, then adding 10-15 times the volume of 4° C. pre-cooled deionized water to terminate the reaction, and centrifuging and washing the solution several times to obtain a camellia oleifera cellulose nanocrystal suspension.
8. The method for preparing size-controlled cellulose nanocrystals using Camellia oleifera according to claim 1, characterized in that: The step S7 specifically comprises: purifying the prepared cellulose nanocrystals by dialysis, placing the oil-tea camellia cellulose nanocrystal suspension into a dialysis bag, dialysing with deionized water until the pH of the suspension is neutral, and then performing ultrasonic dispersion treatment to obtain a purified oil-tea camellia cellulose nanocrystal aqueous solution; the molecular weight cut-off of the dialysis bag is 8000-14000Da; and the ultrasonic treatment is performed in an ice bath, the ultrasonic power is 200-600w, and the ultrasonic time is 2-10min.
9. The method for preparing size-controlled cellulose nanocrystals using Camellia oleifera according to claim 4, characterized in that: In step S3, the material-liquid ratio of cattail oil tea powder to distilled water is 1g:5mL-1g:50mL; the acidic reagent added dropwise is hydrochloric acid, sulfuric acid or nitric acid, with a concentration of 0.1-1mol / L; the appropriate pH range after adjustment is 1-3; the centrifugation conditions are: speed 2000-5000rpm, centrifugation time is 2-8min; the drying conditions are: drying at 40-90°C for 3-12h.
10. The method for preparing size-controlled cellulose nanocrystals using Camellia oleifera according to claim 7, characterized in that: The acidic solution selected in step S6 includes an inorganic acid and an organic acid, the inorganic acid includes sulfuric acid, hydrochloric acid or phosphoric acid, and the organic acid includes formic acid or oxalic acid; the material-liquid ratio of chemically purified camellia oleifera cellulose to the acidic solution is 1g:10mL-1g:50mL; the centrifugation condition is 8000-12000rpm for 8-30min.